Supporting Factors in the Implementation of Smart Governance through E-Performance of the Regional Civil Service Agency of Sidoarjo Regency - Chiqmah, Zachiyatul; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2019)
The availability of adequate resources, regulations, budget funds, facilities and infrastructure is an important component in the implementation of e-government. The government is required to provide quality services to the community to create goals in improving the welfare of the community. One effort to improve government performance is through smart city. One of the applications of smart city in the government is realized by E-Kinerja conducted by the Sidoarjo Regency Regional Civil Service Agency. In its application there are still problems including the lack of ability of human resources (HR) apparatus caused by age, low desire to learn technology, and low levels of education. The purpose of this study is to explain and analyze the Implementation of Smart Governance through E-Kinerja in the Sidoarjo Regency Regional Civil Service Agency. This type of research is a qualitative descriptive study. Data collection techniques in this study used observation, interviews and documentation. Data analysis techniques in this study used data collection, data reduction, data presentation and data verification. The results of this study indicate that the supporting factors in the implementation of E-Kinerja in the Sidoarjo Regency Personnel Agency, (1) telecommunications infrastructure, are adequate because they are equipped with e-performance applications that can be accessed via private mobile phones of each civil servant. (2) the availability of funds and budget for the implementation of e-performance applications funded by the Sidoarjo Regency Regional Budget. (3) written legal instruments regarding the application of e-performance